Regulatory single nucleotide polymorphisms at the beginning of intron 2 of the human KRAS gene; Journal of Biosciences; Vol. 407, iss. 5 - Antontseva E. V. Elena Vyacheslavovna; Matveeva M. Yu. Marina Yurjevna; Bondar N. P. Natalia Petrovna; Kashina E. V. Elena Valentinovna; Leberfarb E. Yu. Elena Yurjevna; Bryzgalov L. O. Leonid Olegovich; Gervas P. A. Polina Anatolevna; Ponomareva A. A. Anastasiya Alekseevna; Cherdyntseva N. V. Nadezhda Viktorovna; Orlov Yu. L. Yury Lvovich; Merkulova T. I. Tatjyana Ivanovna (2015, 2015)
Title screen